The Contagion Effect and the Response of the Eurozone to the Sovereign Debt Problem - Claudiu Peptine; Claudiu Gabriel Tiganas; Dumitru Filipeanu (CES Working Papers, 2013)
This paper addresses a number of phenomena that characterize the euro area, one of them being the contagion effect. This is one of the mechanisms by which financial instability becomes so widespread that the crisis reached global dimensions. The following lines argue that contagion plays a crucial role in exacerbating the sovereign debt problems in the Eurozone. Consequently, the management of the crisis by the competent authorities should focus on policy measures that are able to mitigate the contagion. Therefore, many of the European Central Bank interventions (ECB) in the European Union were motivated by the need for understanding and mitigating the contagion phenomenon.
Keywords: E44; F34; 330; international financial contagion; crisis; macroeconomic indicators; fiscal policies; sovereign debts Romania